Empagliflozin Improves Liver Steatosis and Fibrosis in Patients with Non-Alcoholic Fatty Liver Disease and Type 2 Diabetes: A Randomized, Double-Blind, Placebo-Controlled Clinical Trial - Chehrehgosha, Haleh; Sohrabi, Masoud Reza; Ismail-Beigi, Faramarz; Malek, Mojtaba; Reza Babaei, Mohammad; Zamani, Farhad; Ajdarkosh, Hossein; Khoonsari, Mahmood; Fallah, Afshin Eshghi; Khamseh, Mohammad E. (Diabetes therapy, 2021)
Introduction To evaluate the efficacy of empagliflozin compared to pioglitazone in patients with non-alcoholic fatty liver disease (NAFLD) and type 2 diabetes (T2DM). Methods In this prospective randomized, double-blind, placebo-controlled trial, we assigned 106 patients with NAFLD and T2DM to receive empagliflozin 10 mg ( n = 35), pioglitazone 30 mg ( n = 34), or placebo ( n = 37) for 24 weeks. Liver fat content and liver stiffness were measured using fibroscans. Body composition assessment was performed by dual-energy x-ray absorptiometry (DEXA) scans. The primary end point was change from baseline in liver steatosis, using the controlled attenuation parameter (CAP) score. Results A borderline significant decrease in CAP score was observed with empagliflozin compared to placebo, mean difference: − 29.6 dB/m (− 39.5 to − 19.6) versus − 16.4 dB/m (− 25.0 to − 7.8), respectively; p = 0.05. Using multivariate analysis, we observed a significant reduction in the placebo-corrected change in liver stiffness measurement (LSM) with empagliflozin compared to pioglitazone: − 0.77 kPa (− 1.45, − 0.09), p = 0.02, versus 0.01 kPa (95% CI − 0.70, 0.71, p = 0.98), p for comparison = 0.03. Changes in serum aspartate aminotransferase (AST) and alanine aminotransferase (ALT), fasting insulin, homeostatic model assessment for insulin resistance (HOMA-IR), HOMA2-IR, fibrosis-4 index (FIB4 index), NAFLD fibrosis score, aspartate aminotransferase to platelet ratio index (APRI), android/gynecoid ratio (A/G ratio), and skeletal muscle index (SMI) were comparable between the two treatment groups, while significant reductions of the body weight and visceral fat area were observed only in the empagliflozin group ( p < 0.001 and p = 0.01, respectively) and both were increased in the placebo and pioglitazone groups. There were no serious adverse events in either group. Conclusion Treatment for 24 weeks with empagliflozin, in contrast to pioglitazone, was associated with improvement of liver steatosis and fibrosis in patients with NAFLD and T2DM. In addition, body weight and abdominal fat area were decreased in the empagliflozin group. Trial Registration Iranian Registry of Clinical Trials (IRCT), IRCT20190122042450N3.